(untitled) (Jurnal Pendidikan Fisika, 2026)
The development of scientific literacy has become a central goal of physics education in the twenty-first century, particularly in response to persistent gaps in students’ ability to apply scientific knowledge to real-life contexts. In Indonesia, students’ scientific literacy remains below international benchmarks, highlighting the urgency of developing contextual and culturally relevant learning resources. The purpose of this study is to develop a physics companion book based on Takalar local wisdom to enhance senior high school students’ scientific literacy and support the achievement of Sustainable Development Goal 4 (Quality Education). The study employed the Plomp development model, consisting of three main phases: preliminary research, prototyping, and assessment. The preliminary phase involved a needs analysis and a curriculum study to identify opportunities to integrate local culture into physics learning. Experts in content, media, and language designed and validated the book during the prototyping phase. The assessment phase tested the practicality and effectiveness of the book through a limited trial with 95 senior high school students in Takalar. Data were collected using validation sheets, scientific literacy tests, and student response questionnaires. Results indicated a high level of validity (Gregory index V = 1.00) and very positive student responses (77%). Empirical findings show an improvement in students’ scientific literacy, with the majority reaching moderate (66%) to adequate levels after implementation. The novelty of this study lies in the systematic integration of local wisdom into a physics companion book using a comprehensive development model, accompanied by empirical evaluation of scientific literacy outcomes and explicit alignment with SDG 4. This research is expected to make a real contribution to the provision of valid, practical, and effective teaching materials to strengthen science literacy, 21st-century skills, and the achievement of SDG 4.